cho x khác y
x2+y=y2+x
Tính giá trị biểu thức: A=( x2+y2+xy)/xy-1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(=\left(x-y\right)\left(x+y\right)\)
\(=74\cdot100=7400\)
c: \(=\left(x+2\right)^3\)
\(=10^3=1000\)
a) \(=\left(x-y\right)\left(x+y\right)\)
Thay \(x=87;y=13\) ta đc: \(\left(87-13\right)\left(87+13\right)=74\cdot100=7400\)
b)\(=\left(x-y\right)\left(x^2+xy+y^2\right)=x^3-y^3\)
Thay \(x=10;y=-1\) ta đc:
\(10^3-\left(-1\right)^3=1000-1=999\)
c)\(=\left(x+2\right)^3\)
Thay \(x=8\) ta đc: \(\left(8+2\right)^3=10^3=1000\)
d)\(=x^2-8x+16+1=\left(x-4\right)^2+1\)
Thay \(x=104\) ta đc: \(\left(104-4\right)^2+1=100^2+1=10001\)
\(a,A=x^2+y^2\\=x^2-2xy+y^2+2xy\\=(x-y)^2+2xy\\=2^2+2\cdot1\\=4+2\\=6\)
\(b,x+y=1\\\Leftrightarrow (x+y)^3=1^3\\\Leftrightarrow x^3+3x^2y+3xy^2+y^3=1\\\Leftrightarrow x^3+3xy(x+y)+y^3=1\\\Leftrightarrow x^3+3xy\cdot1+y^3=1\\\Rightarrow A=1\)
a) Ta có:
\(x-y=2\)
\(\Rightarrow\left(x-y\right)^2=2^2\)
\(\Rightarrow x^2-2xy+y^2=4\)
Mà: \(xy=1\)
\(\Rightarrow\left(x^2+y^2\right)-2\cdot1=4\)
\(\Rightarrow x^2+y^2=4+2\)
\(\Rightarrow x^2+y^2=6\)
b) Ta có:
\(x+y=1\)
\(\Rightarrow\left(x+y\right)^3=1^3\)
\(\Rightarrow x^3+3x^2y+3xy+y^3=1\)
\(\Rightarrow x^3+3xy\left(x+y\right)+y^3=1\)
Mà: x + y = 1
\(\Rightarrow x^3+3xy\cdot1+y^3=1\)
\(\Rightarrow x^3+3xy+y^3=1\)
a: \(A=x^2+y^2=\left(x+y\right)^2-2xy=15^2-2\cdot50=115\)
c: \(x-y=\sqrt{\left(x+y\right)^2-4xy}=\sqrt{15^2-4\cdot50}=5\)
\(C=x^2-y^2=\left(x+y\right)\left(x-y\right)=15\cdot5=75\)
Ta có \(x^2+y^2+xy+x=y-1\)
\(\Leftrightarrow2x^2+2y^2+2xy+2x-2y+2=0\)
\(\Leftrightarrow\left(x+y\right)^2+\left(x+1\right)^2+\left(y-1\right)^2=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}x+y=0\\x+1=0\\y-1=0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=-1\\y=1\end{matrix}\right.\)
\(\Rightarrow B=\left(-1+1-1\right)^{2023}\) \(=\left(-1\right)^{2023}\) \(=-1\)
a: \(A=x^2+y^2=\left(x+y\right)^2-2xy=15^2-2\cdot50=125\)
b:\(B=x^4+y^4\)
\(=\left(x^2+y^2\right)^2-2x^2y^2\)
\(=125^2-2\cdot2500\)
=10625
c: \(x-y=\sqrt{\left(x+y\right)^2-4xy}=\sqrt{15^2-4\cdot50}=5\)
\(C=x^2-y^2=\left(x-y\right)\left(x+y\right)=15\cdot5=75\)
Ta có ( x + y ) 2 = x 2 + y 2 + 2 x y = 4 − 2 3 = ( 3 − 1 ) 2 ⇒ x + y = 3 − 1.
Suy ra P = x + y = 3 − 1 k h i x + y ≥ 0 1 − 3 k h i x + y < 0 .
\(x^2+y=y^2+x\Leftrightarrow x^2-y^2-\left(x-y\right)=0\)
\(\Leftrightarrow\left(x-y\right)\left(x+y\right)-\left(x-y\right)=0\)
\(\Leftrightarrow\left(x-y\right)\left(x+y-1\right)=0\)
\(\Rightarrow x+y=1\)
Ta có: \(A=\frac{x^2+y^2+xy}{xy-1}\Rightarrow A+1=\frac{x^2+y^2+xy}{xy-1}+1\)
\(\Rightarrow A+1=\frac{x^2+2xy+y^2-1}{xy-1}=\frac{\left(x+y\right)^2-1}{xy-1}=\frac{0}{xy-1}=0\)
\(\Rightarrow A=-1\)